2020
DOI: 10.1002/hsr2.196
|View full text |Cite
|
Sign up to set email alerts
|

Birthweight and gestational age‐specific neonatal mortality rate in tertiary care facilities in Eastern Central Uganda

Abstract: Background An estimated 2.8 million neonatal deaths occur each year globally, which accounts for at least 45% of deaths in children aged less than 5 years. Birthweight and gestational age‐specific mortality estimates are limited in low‐resource countries like Uganda. A deeper analysis of mortality by birthweight and gestational age is critical in identifying the cause and potential solutions to decrease neonatal mortality. Objectives We studied mortality before discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The studies were conducted from 2012 to 2020 among more than 11 Eastern Africa countries including 12 from Ethiopia represented by 14 studies [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Tanzania [ 14 , 45 , 46 , 47 ] and Uganda [ 12 , 48 , 49 , 50 ] represented by 04 studies, Besides, Burundi [ 51 , 52 ] and Eretria [ 53 , 54 ] represented by 02 studies. While Malawi [ 55 ], Kenya [ 56 ], Zambia [ 24 ], Sudan [ 25 ], Mozambique [ 57 ], and Zimbabwe [ 58 ] are represented by 01 studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies were conducted from 2012 to 2020 among more than 11 Eastern Africa countries including 12 from Ethiopia represented by 14 studies [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Tanzania [ 14 , 45 , 46 , 47 ] and Uganda [ 12 , 48 , 49 , 50 ] represented by 04 studies, Besides, Burundi [ 51 , 52 ] and Eretria [ 53 , 54 ] represented by 02 studies. While Malawi [ 55 ], Kenya [ 56 ], Zambia [ 24 ], Sudan [ 25 ], Mozambique [ 57 ], and Zimbabwe [ 58 ] are represented by 01 studies.…”
Section: Resultsmentioning
confidence: 99%
“…While Malawi [ 55 ], Kenya [ 56 ], Zambia [ 24 ], Sudan [ 25 ], Mozambique [ 57 ], and Zimbabwe [ 58 ] are represented by 01 studies. Regarding study design, 13 studies employed retrospective cohort [ 12 , 14 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 56 , 57 ], whereas 07 prospective cohort studies [ 31 , 32 , 46 , 47 , 48 , 49 , 50 ], 01 case-control type [ 36 ], and 11 cross-sectional design [ 24 , 25 , 33 , 34 , 35 , 51 , 52 , 53 , 54 , 55 , 58 ]. All studies included in this review were observational studies which were conducted in the hospital with sample sizes ranging from 100 participants reported from a study in Ethiopia and Sudan [ 25 , 36 ], and 29811 from Uganda [ 12 ] respectively ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in Uganda states that for every 1,000 grams increase in birth weight, the risk of mortality decreases by 0.016. This Uganda study also states that the mortality rate is highest for babies born with birth weights between 500-999 grams (336/1000 live births) (Mubiri et al, 2020). In Indonesia, a study found that the risk for neonatal mortality is 9.89 times higher for babies with low birth weight (Suparmi et al, 2016).…”
Section: Neonatal Medical Profilementioning
confidence: 88%